Effects of amylose and amylopectin molecular structures on starch electrospinning. (15th November 2022) - Cao, Panpan; Wu, Gaosheng; Yao, Zhijie; Wang, Zihan; Li, Enpeng; Yu, Shiyao; Liu, Qiaoquan; Gilbert, Robert G.; Li, Songnan
Abstract: The role of amylose content in electrospinning starch nanofibres is well understood, but that is not the case for the roles of the molecular structures of amylose and amylopectin. Here, correlations between starch molecular-structure parameters and electrospinnability evaluation indices (average droplet number, average bead number, and average fibre diameter) and dope properties (shear viscosity, conductivity, and surface tension) were examined. Starches with lower amounts of short amylopectin chains, higher amounts of either/or long amylopectin chains and/or lower degree of branching showed decreased viscosity of the electrospinning dopes, and resulted in a reduced average droplet number of electrospun fibre mats. The molecular sizes of amylose and whole starch, and the average degree of polymerization for amylose chains, all correlated with the shear viscosity and surface tension of dopes, and thus influenced the average fibre diameter. This expands the current understanding between amylopectin molecular structure and starch electrospinning, thereby assisting a better choice of starches for desired electrospinnability properties. Graphical abstract: Unlabelled Image